Different patterns and specific outcomes of large-vessel involvements in giant cell arteritis. (September 2019) - de Boysson, Hubert; Liozon, Eric; Espitia, Olivier; Daumas, Aurélie; Vautier, Mathieu; Lambert, Marc; Parienti, Jean-Jacques; Granel, Brigitte; Dumont, Anael; Sultan, Audrey; Manrique, Alain; Saadoun, David; et al.
Abstract: Large-vessel involvement (LVI) in giant cell arteritis (GCA) includes different clinical and imaging patterns that are rarely described separately at diagnosis and whose specific cardiovascular outcomes are unknown. We conducted a nationwide retrospective study and included GCA patients with LVI demonstrated on imaging at diagnosis between 2007 and 2017. We analyzed the prognosis of three different imaging patterns of LVI present at diagnosis, with some of them overlapping but with the first one present in all patients: 1) inflammation of the aorta and/or its branches; 2) dilation of the aorta; and 3) stenosis of the aortic branches. A control group of GCA patients without LVI was constituted. We included 183 patients with LVI and 105 controls without LVI. Altogether, among the 183 patients who all showed inflammation of the aorta and/or its main branches, concomitant aortic dilation and large-vessel stenosis were observed in 27 (15%) and 55 (30%) patients, respectively. During the follow-up period, new cardiovascular events occurred in 49% and 11% of LVI patients and controls, respectively (p < 0.0001). Inflammation of the aorta and/or its branches (HR: 3.42 [2.09–5.83], p < 0.0001) and large-artery stenosis (HR: 2.75 [1.80–4.15], p < 0.0001) were independent predictive factors of new cardiovascular events. Conversely, the use of an immunosuppressant besides corticosteroids was a protective factor against new cardiovascular events (HR: 0.44 [0.29–0.66], p < 0.0001) and the development of aortic dilation (HR: 0.43 [0.23–0.77], p = 0.005). This study suggests different forms of cardiovascular events according to the initial imaging pattern of LVI. Highlights: Large-vessel involvements include aortitis, aorta dilation and vascular stenoses. These patterns exhibit different outcomes and prognoses. More cardiovascular events occur in patients with initial large-vessel involvement. Large-vessel stenosis was associated with the poorest outcomes. Immunosuppressants might have a protective impact on new cardiovascular events.